Predicting aerosol size distribution development in absorption columns. (31st December 2018) - Majeed, Hammad; Hillestad, Magne; Knuutila, Hanna; Svendsen, Hallvard F.
Highlights: Droplet size distribution development predicted for absorption columns. Outlet size distribution becomes narrower than the inlet distribution. Outlet size distribution width increases with droplet number concentration. Higher CO2 content leads to larger droplets and narrower distributions. Abstract: There are two main mechanisms for amine emissions from absorption columns. The first is connected to the volatility of amine, determining the gaseous concentration. The second mechanism is via aerosol droplets containing amine. Recently, aerosol based emissions in g/Nm 3 were identified from typical PCCC plants (Khakharia et al., 2013). Mechanisms for aerosol formation, aerosol growth, emissions related to aerosol formation and in particular the development and testing of aerosol emission reducing systems for amine based post-combustion, are presently under study. However, there is still limited information available in the open literature. In some recent studies, the effect of water wash and demisting equipment was studied and results indicate that aerosol droplets still pass through these equipment sections. On the other hand, water wash systems help in increasing the droplet size as well as reducing both gas phase and aerosol based emission. However, this does not completely solve the problem (da Silva et al., 2013). Recently, modeling studies for mono-disperse droplet swarms are published (Majeed et al., 2017a, 2017b; Majeed and Svendsen, 2018a, 2018b). However, results for multi-sized droplet swarms and for droplet size distributions are missing. Droplets can be described by their size, temperature and composition. All droplet populations will have a size distribution, being just as important as any other parameter. Performing a distribution analysis is the best way to determine the sizes of droplets in a particular stream at any point in an absorber. In this work, both a multi-droplet size model and a size distribution model are implemented. The multi-droplet size model is used for validation and results are in line with findings from the mono-disperse model by (Majeed et al., 2017b; Majeed and Svendsen, 2018a). Droplet distribution model results are compared with experimental data from Toshiba (Fujita, 2017) and reasonable agreement is found. The development of inlet droplet distributions through an absorber and water-wash system is modelled for several flue gas sources. It is found that the outlet distribution mean size increases with inlet gas CO2 concentration. Similarly, the outlet mean droplet size decreases and the size distribution width increases with incoming droplet number concentration.